Exploration of the anti-gastric cancer potential of phytocompounds from Cinnamomum tamala using Network Pharmacology Approach - PAUDEL, DIPAK; Koirala, Santosh; Bhandari, Dhaka Ram; Pokhrel, . Megh Raj; Adhikari, Achyut (BIBECHANA, 2026)
Plants have long served as vital sources of bioactive compounds for food, spice, and medicine. Cinnamomum tamala, a traditional Nepali spice and herbal remedy, has shown promising pharmacological potential, including anticancer properties. This study aimed to explore the anti-gastric cancer potential of phytoconstituents from Cinnamomum tamala using a network pharmacology-based in silico approach. The GC–MS analysis of methanolic extracts of three plant samples collected from different locations revealed thirty compounds, among which sixteen were common volatile constituents. Four major compounds, cinnamaldehyde, cinnamyl acetate, linalool, and caryophyllene oxide, were selected for further computational analysis. A total of 105 target proteins of the compound and 1,012 gastric cancer-associated genes were identified, revealing 48 overlapping targets. Protein–protein interaction (PPI) network analysis highlighted PTGS2, TLR4, NR3C1, RELA, and JAK2 as key hub proteins. KEGG pathway enrichment indicated significant involvement of the PD-L1 expression and PD-1 checkpoint pathway in cancer, Th1 and Th2 cell differentiation, and the NF-κB signaling pathway. These findings suggest that compounds of Cinnamomum tamala may exert anti-gastric cancer effects by modulating immune checkpoints and inhibiting oncogenic signaling pathways, thereby promoting apoptosis of gastric cancer cells. This study provides molecular insights supporting the potential therapeutic application of Cinnamomum tamala in gastric cancer treatment.